Pollution, Energy and Growth: Evidence from Post-Communist Countries - Sadikov, Avazbek; Kasimova, Nargiza; Isaeva, Arletta; Khachaturov, Anastas; Salahodjaev, Raufhon (International Journal of Energy Economics and Policy, 2020)
This paper investigates the empirical relationship between carbon dioxide emissions, economic growth and energy use in post-communistic countries during 1990-2018. Pedroni’s (1999) panel cointegration test discovered cointegrating relationship between the variables. To distinguish short- and long-term effect, as well as to account for homogeneity caused by previous common socio-political system and current country specific characteristics, Pesaran’s (1999) Pooled Mean Group estimator is employed. PMG estimates identified short- and long-term relationship between energy use and CO2 emissions and short-term relationship between CO2 emissions and economic growth. Finally, the Dumitrescu and Hurlin’s (2012) Granger non-causality test for heterogeneous panels revealed bidirectional causality between CO2 emissions, energy use and economic growth. Keywords: CO2 emissions, economic growth, energy consumption, post-communistic countries. JEL Classifications: C23, P18, O47 DOI: https://doi.org/10.32479/ijeep.9637